Radiant Emptiness: Three Seminal Works by the Golden Pandita Shakya Chokden - Komarovski, Yaroslav (Oxford University Press, Incorporated, 2019)
In Radiant Emptiness, Yaroslav Komarovski offers an annotated translation of three seminal works on the nature and relationship of Yogacara and Madhyamaka, by Serdok Penchen Shakya Chokden (1428-1507).